PENERAPAN BRAND PLACEMENT BISKUIT BETTER MELALUI MEDIA FILM - Ni Luh Putu Eka Putri Saraswati; Dini Salmiyah Fithrah Ali (Dialektika, 2017)
Brand Placement is a marketing strategy that allows brand name to be placed in any media program such as television program, film,etc. This strategy has a purpose to remind and increasing consument awareness about the brand name and also increasing the visibility of the brand. Film is one of the media that usually used in brand placement because of the smooth characteristic so that brand will be placed naturally with the plot of story and create a good perception for audience. This research is a qualitative descriptive research to analyze the perception of film community member in Telkom University Bandung (FFT) about the brand placement of BETTER biscuit in Koala Kumal Movies. This research use a focus group discussion as a method. The result of the research is that brand placement is doing a great job as a reminder. The member of Telkom University film community has a good perception about the placement and they could tell the characteristic of BETTER in Koala Kumal movies clearly.